Characterization of Prophages in Leuconostoc Derived from Kimchi and Genomic Analysis of the Induced Prophage in Leuconostoc lactis - Kim, Song-Hee; Park, Jong-Hyun (Journal of microbiology and biotechnology, 2022)
has been used as a principal starter in natural kimchi fermentation, but limited research has been conducted on its phages. In this study, prophage distribution and characterization in kimchi-derived strains were investigated, and phage induction was performed. Except for one strain, 16 strains had at least one prophage region with questionable and incomplete regions, which comprised 0.5-6.0% of the bacterial genome. Based on major capsid protein analysis, ten intact prophages and an induced incomplete prophage of CBA3626 belonged to the family and were similar to Lc-Nu-like, sha1-like, phiMH1-like, and TPA_asm groups. Bacterial immunology genes, such as superinfection exclusion proteins and methylase, were found on several prophages. One prophage of CBA3626 was induced using mitomycin C and was confirmed as belonging to the family. Homology of the induced prophage with 21 reported prophages was not high (< 4%), and 47% identity was confirmed only with TPA_asm from sp. isolate ct3pk4. Therefore, it is suggested that from kimchi had diverse prophages with less than 6% genome proportion and some immunological genes. Interestingly, the induced prophage was very different from the reported prophages of other species.